Miyazaki's Hybrid Worlds and Their Riddle-Stories: Western Tropes and Kishōtenketsu - Arnavas, Francesca; Bellini, Mattia (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2023)
“Fairy tales begin with conflict because we all begin our lives with conflict,” famously states Jack Zipes. And yet, this statement does not always seem to apply to non-Western story structures, such as the Asian kishōtenketsu, which implies a story development that does not necessarily revolve around conflicts. In many of Hayao Miyazaki’s movies (e.g., My Neighbor Totoro; Spirited Away, The Secret World of Arietty), it is possible to detect, on the one hand, the kishōtenketsu-based plot, and,on the other hand, the widespread presence of Western fairy-tale tropes. Conflicts in traditional Western fairy tales may sometimes manifest in the form of riddles to solve. Although Miyazaki’s stories do not shun away from riddles, how do these riddles relate to conflicts? How are Western and Asian story structures bound together in Miyazaki’s narratives, and what effects does this hybridization generate in their audiences? This article argues that: 1.) Riddles based on Western fairy tales in Miyazaki’s work do not necessarily involve conflicts, and are recast and re-elaborated in highly unusual ways; and 2.) The employment of these unusual patterns, mixing up together Oriental and Occidental frames of reference, gives rise to stories that puzzle the mind of spectators, working as complex narrative riddles.